A framework for evaluating the dynamic impacts of the Brazilian Urban Mobility Policy for transportation socioeconomic systems: A case study in Rio de Janeiro. Issue 4 (1st October 2020) - Fontoura, Wlisses B.; Ribeiro, Glaydston M.; Chaves, Gisele De L. D.
ABSTRACT: Transportation planning is necessary to meet the demand of a given region considering the dimensions of urban space and the complexity of the activities developed on it. In addition to planning, the government intervention through policies to provide an adequate flow of people and goods to meet population demand is also important. In Brazil, the Brazilian Urban Mobility Policy (BUMP) aims to integrate different modes of transportation and improve accessibility and urban mobility. Thus, this study presents a decision support model, using System Dynamics as a modeling and simulation tool, to evaluate the impacts of BUMP implementation, focusing on environmental, economic and traffic variables. In order to verify the applicability of the proposed model, a case study was carried out in the city of Rio de Janeiro. The results indicate the importance of BUMP implementation to reduce negative externalities and, consequently, to increase the efficiency of the urban transport system.